2014
DOI: 10.17214/aot.45256
|View full text |Cite
|
Sign up to set email alerts
|

Çukurova bölgesinin süpernümerer diş karakteristikleri: çok merkezli retrospektif bir çalışma

Abstract: [Abstract in English is at the end of the manuscript] GİRİŞDental arkta belirli bir bölgede olması gerekenden daha fazla sayıdaki dişlere süpernümerer dişler denir.1 Sü-pernümerer dişler daimi dentisyonda daha sık olmakla beraber, hem daimi hem de süt dentisyonda gözlene-bilmektedir.2 Hiperdonti terimi, süpernümerer diş içeren dentisyonu tanımlamak için kullanılır.2 Süpernümerer dişlerin etyolojisi tam olarak bilinmemekle beraber, diş tomurcuğunun tamamen ikiye ayrılması veya normal sayıdaki diş tomurcuğu oluş… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…The other parameters of the study were related to erupted supernumerary teeth. Our findings were similar to that of Altuğ et al ( 1 ) but slightly different to that of Tatlı et al ( 20 ). On the other hand, Vahid-Dastjerdi et al ( 30 ), who had investigated supernumerary teeth in orthodontic patients, have found that the prevalence of supernumerary teeth was 0.74% being highest in Class III malocclusions and lowest in Class II malocclusions.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…The other parameters of the study were related to erupted supernumerary teeth. Our findings were similar to that of Altuğ et al ( 1 ) but slightly different to that of Tatlı et al ( 20 ). On the other hand, Vahid-Dastjerdi et al ( 30 ), who had investigated supernumerary teeth in orthodontic patients, have found that the prevalence of supernumerary teeth was 0.74% being highest in Class III malocclusions and lowest in Class II malocclusions.…”
Section: Discussionsupporting
confidence: 80%
“…Multiple supernumerary teeth in the same person is a rare occurrence. This condition may be related to a syndrome or a developmental disorder ( 6 , 20 , 21 ). Thus, patients having multiple supernumerary teeth should be carefully evaluated for the presence of a genetic disorder.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations